RESPONSE OF DIFFERENT GENOTYPES OF BROILERS TO LYSINE SUPPLEMENTATION RAISED UNDER PRACTICAL CONDITION - Indarsih, B.; Tamsil, M.H. (Diponegoro University, 2012)
This study evaluated lysine supplementation of 4 to 42 day of age of two commercial broilergenotypes (Arbor Acres and Lohmann). Four hundred and fifty day-old chicks were sexed andrandomly distributed into 60 bamboo pens each 2 m2. A starter commercial diet as a basal diet wassupplemented with lysine mono-HCL in a 2x2x5 factorial arrangement with lysine levels of 0.0, 0.5,1.0, 1.5 and 2.0 g/kg fed from 4-21 days of age, and then followed by a finisher diet fed from 22-42days of age. Feed consumption, body weight gain and FCR were determined on weekly basis. On d 43of experiment, 4 birds per each replicate were processed for carcass parameters. Results of the studyrevealed that lysine supplementation in a starter commercial diet increased significantly carcass weight(P<0.05. Improved breast meat and lower abdominal fat were found in lysine supplementation. ArborAcres broilers response more efficient in low lysine whilst Lohmann broilers were better in a higherlevel of lysine.